Impact of Social Media on Child Morality in Indonesia - Supardi Supardi; Amroeni Drajat; M, Reza Alfikri (Jurnal Ilmiah Wahana Pendidikan, 2023)
Bigo Live is a broadcast application in the form of the most popular live streaming video for IOS and ANDROID operating systems with the number of users in Indonesia reaching 10 million users. This research was carried out using the mixed method, which combines qualitative and quantitative methods. The case study of this study was carried out in 2 locations covering Indonesia, namely Medan and DKI Jakarta. The results showed that there was a significant impact between Pornography and Porn Content Action on Bigo Live on Child Morality in Indonesia. The picture of deviant morality in adolescents in Indonesia shows that there are deviant behaviors, although it is dominated by the light deviant behavior of 53 respondents (68.8%). Thus the results are accepted, so it can be said that the cultivation theory of exposure to mass media towards changes in the behavior of viewers is proven to have an effect between the frequency of watching pornography and pornography on Bigo Live social media on the deviant (sexual) morality of teenagers in Indonesia. Research implications, it is expected for teachers, parents, guardians and community leaders from the results of this study to be used as an evaluation material to build the personality of adolescents and teachers and lecturers always provide information to students to use the internet only for positive things. The existence of this research is expected to be one of the considerations for Bigo Live's Social Media to be disciplined again, by adding an automatic and applicable filter system for users who abuse Bigo Live's social media applications so as not to damage the morality of Indonesian children.